A Theory of Demographically Targeted Repression. (August 2020) - Rozenas, Arturas
People from specific ethnic, religious, or other externally identifiable groups are often subjected to harsher repression than others. This phenomenon of demographically targeted repression is often viewed as a result of xenophobia. I provide a rationalist explanation of demographic targeting to understand why this form of repression is employed even without xenophobic motives. Building on the empirical literature, I model an environment where a threat of repression may motivate people to oppose the regime defensively. I show that, in such conditions, the regime may use demographic targeting to undermine cross-group collective action. The model explains when demographic targeting is used and how it shapes the behavior and identity of citizens. I use the model to make sense of certain aspects of repression policy in China.